2019
DOI: 10.1097/spv.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Contamination of Voided Urine Specimen in Women With Pelvic Organ Prolapse

Abstract: Objectives The primary aim of this study was to determine if urine cultures are more likely to be contaminated in women with pelvic organ prolapse (POP). The secondary aim was to evaluate the test characteristics of a urine dipstick in women with POP. Methods A retrospective cohort study was conducted of women who presented to the urogynecology clinic between September 1, 2017, and August 31, 2018. Associations between the presence of POP and contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Previous research has demonstrated that overweight and obese female patients have an increased likelihood of providing a contaminated clean catch specimen, 9 also that women with pelvic organ prolapse would have increased rates of contaminated clean catch specimens. 10 Our study provides additional information for interpreting urine specimen results from 2 collection methodologies, as well as guidance for clinical scenarios specific to a urogynecology patient population.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has demonstrated that overweight and obese female patients have an increased likelihood of providing a contaminated clean catch specimen, 9 also that women with pelvic organ prolapse would have increased rates of contaminated clean catch specimens. 10 Our study provides additional information for interpreting urine specimen results from 2 collection methodologies, as well as guidance for clinical scenarios specific to a urogynecology patient population.…”
Section: Discussionmentioning
confidence: 97%
“…Parasites that may be found in urinary sediments include Trichomonas vaginalis [11,61], Enterobius vermicularis [11,62], and Schistosoma haematobium (Chronically infected adults pass few eggs in the urine, which are often missed when current diagnostic methods are used) [11,63]. Except for S. haematobium, parasites and parasitic ova are usually present in urine sediment as a result of vaginal or fecal contamination [64,65]. The next section will briefly focus on the parasitic contamination which can be detected in urinalysis.…”
Section: Parasitology Urinalysismentioning
confidence: 99%
“…In urine specimens which actually come from female patient, it is believed that the presence of T. vaginalis represents vaginal contamination [92], specifically is contaminated by organisms from the vaginal discharge [64,65]. Despite the fact that the midstream clean-catch technique is commonly used for urine collection [42,64], contaminated urine cultures are commonly happening with distressing regularity [64,65].…”
Section: Trichomonas Vaginalis and How It Contaminated Urinementioning
confidence: 99%
“…One study demonstrated that women with POP are more likely to have contaminated urine cultures from a voided specimen than from a straight catheter specimen (odds ratio, 1.89; 95% confidence interval, 1.20-2.99). 5 Our study assessed the agreement between the results of urinalysis and urine culture obtained from a clean-catch versus a straight catheter urine specimen among women who underwent vaginal surgery for POP.…”
Section: Why This Mattersmentioning
confidence: 99%
“…However, this may not be accurate in women with prolapse and particularly in women who recently have undergone vaginal surgery. One study demonstrated that women with POP are more likely to have contaminated urine cultures from a voided specimen than from a straight catheter specimen (odds ratio, 1.89; 95% confidence interval, 1.20–2.99) 5 …”
mentioning
confidence: 99%